2015
DOI: 10.1017/ice.2015.38
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medicare’s Hospital-Acquired Condition Policy on Infections in Safety Net and Non–Safety Net Hospitals

Abstract: BACKGROUNDPolicymakers may wish to align healthcare payment and quality of care while minimizing unintended consequences, particularly for safety net hospitals.OBJECTIVETo determine whether the 2008 Centers for Medicare and Medicaid Services Hospital-Acquired Conditions policy had a differential impact on targeted healthcare-associated infection rates in safety net compared with non–safety net hospitals.DESIGNInterrupted time-series design.SETTING AND PARTICIPANTSNonfederal acute care hospitals that reported c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
(35 reference statements)
0
23
0
Order By: Relevance
“…The issue of Health Care-Associated Infections (HAIs) continues to be one of the most important public health problems in many countries throughout the world [1,2], and these infections remain a leading cause of morbidity and mortality among hospitalized patients [3] also with an increase consumption of resources and add to cost [4,5]. Central line-associated bloodstream infections (CLABSIs), the majority related with the use of the central venous catheter (CVC) [6,7], are the most important complications in critical care [810] and in cancer settings [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of Health Care-Associated Infections (HAIs) continues to be one of the most important public health problems in many countries throughout the world [1,2], and these infections remain a leading cause of morbidity and mortality among hospitalized patients [3] also with an increase consumption of resources and add to cost [4,5]. Central line-associated bloodstream infections (CLABSIs), the majority related with the use of the central venous catheter (CVC) [6,7], are the most important complications in critical care [810] and in cancer settings [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…2016;37(1): [100][101][102][103] In October 2008, the Centers for Medicare & Medicaid Services halted reimbursement for preventable hospital-acquired conditions (HAC), such as central line-associated bloodstream infections (CLABSI). 1 Although our group's prior work found no impact of this policy on already declining secular trends in CLABSI rates reported by US hospitals as a whole 2 or by safety net status, 3 we did not examine whether a hospital's financial operating margin (OM) impacted its response to the HAC policy. Others have demonstrated that hospitals operating at a financial loss have worse performance in terms of quality measures.…”
mentioning
confidence: 97%
“…In our primary analysis, we used an interrupted time series design to evaluate the impact of the HAC policy on quarterly CLABSI rates reported by hospitals in the lowest (greatest annual loss) and highest (greatest annual profit) quartiles. 2,3 We hypothesized that the potential for financial penalties might have led to a different response to the HAC policy in hospitals operating at a financial loss. Because ventilatorassociated pneumonia (VAP) was not targeted by the HAC policy, this was used as a control condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitals with a total HAC score above the 75th percentile of the total HAC score distribution are subject to payment reduction [3]. An analysis of the preliminary penalties suggested that major teaching hospitals are 2.9 times more likely to be penalized in this program than nonteaching hospitals [4,5]. Additionally, CMS estimates that 56% of major teaching hospitals will be penalized [2].…”
mentioning
confidence: 99%